Hyperpolarization as a mechanism for endothelium-dependent relaxations in the porcine coronary artery. - Nagao, T (1992)
1. The nature of endothelium-dependent relaxations resistant to nitro-L-arginine was investigated in porcine coronary arteries by measuring isometric force and membrane potential in the presence of indomethacin. 2. Bradykinin induced concentration- and endothelium-dependent relaxations and hyperpolarization in tissues contracted with prostaglandin F2 alpha. Nitro-L-arginine did not affect either the relaxations or the hyperpolarization induced by bradykinin. The threshold concentration of bradykinin was the same for the nitro-L-arginine-resistant relaxations and the membrane hyperpolarization. 3. Nitro-L-arginine-resistant relaxations were evoked by several agents (A23187, thrombin and UK 14304) in addition to bradykinin. The amplitude of membrane hyperpolarizations observed with all agents was proportional to that of nitro-L-arginine-resistant relaxations. 4. Thrombin caused more transient relaxations and hyperpolarizations than bradykinin in the presence of nitro-L-arginine. 5. In tissues contracted with high K+ or tetrabutylammonium (a non-selective K(+)-channel blocker), bradykinin inhibited the contractions in a concentration-dependent manner, whereas membrane hyperpolarization was not observed. The relaxations evoked by the kinin were abolished by nitro-L-arginine. 6. These results suggest that endothelium-dependent relaxations which are resistant to nitro-L-arginine are mediated by membrane hyperpolarization in the porcine coronary artery.